Goodpatch : bringing user interfaces with heart to the world - Szymanek, Karolina; Saito, Keita; Koolmees, Marcus; Bode, Paula; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
Goodpatch, founded by Naofumi Tsuchiya, is a leading Japanese company in User Interface (UI) design. Ever since its foundation Naofumi Tsuchiya has dreamt of his company to internationalize and become the number one UI design firm in the World. The lack of strategic intent on expanding internationally leaves that Tsuchiya has to make up his mind upon several dilemmas; how to grow, which market and products/services to focus on, and how to prepare the organization for international expansion given the current structure of human resources, relationships, the Japanese monoculture of the company, and the role and leadership of the founder, which will all affect the choices he needs to make. To make the decision on expanding internationally even more complex Tsuchiya has received an offer of Digital Garage, a web business and marketing company, which has offered to buy a 20% stake of Goodpatch for a price of [yen]100M (approx. $1,000,000).What are the first steps to take to make his dream come true? What factors should Tsuchiya consider in determining his growth strategy? And what response to the offer of Digital Garage would be beneficial for him?
Originally Published InSzymanek, K., Saito, K., Koolmees, M., Bode, P., & Hulsink, W. (2014). Goodpatch: Bringing user interfaces with heart to the world. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Goodpatch -- Case studies; Strategic planning -- Case studies; Business planning -- Case studies